Uncovering the function of CREB regulated transcription coactivator 2 (CRTC2) in rodent brain - Lim, Wei Lee (Nanyang Technological University, 2018)
CRTC2 is potent transcriptional coactivator that undergoes robust nucleo-cytoplasmic shuttling to enhance CREB-mediated transcription in multiple cell types. In hepatocytes and pancreatic islet β-cells, CRTC2 responds to both glucose and incretin signals by activating CREB and upregulating the gene expression critical for glucose homeostasis. In the brain, CRTC2 is expressed in the hypothalamus and hippocampus. To date, the role for CRTC2 in the hippocampus has not been described. In this thesis, we provide evidence that CRTC2 mRNA and protein can be detected in the mouse hippocampus of neonates to adulthood. We show that the CRTC2 protein is localized in both neurons and astrocytes in various hippocampal preparations. However, unlike CRTC1, we provide evidence that CRTC2 in neurons do not undergo activity-dependent nuclear translocation. Chemical stimulation of acute brain slices to promote long-term potentiation (LTP) also did not trigger CRTC2 nuclear accumulation in hippocampal excitatory neurons. Finally, none of the metabolic stimuli we tested in neurons triggered nuclear accumulation of CRTC2. However, we show evidence that CRTC2 localized in hippocampal astrocytes respond to hypoglycemic conditions by accumulating in the nucleus. CRTC2 translocation corresponds to a robust increase in p-CREB133 levels which likely triggers transcription of CREB target genes associated with glycogen metabolism. Finally, we provide evidence that CRTC2 protein associates with the mitochondria and may serve to modulate expression of mitochondrial genes.